McKenzie Exercise for Reducing Low Back Pain Complaints in Office Worker: An Evidence-based Case Report - Pahlavie, Bonnie Medana; Soemarko, Dewi S; Widyahening, Indah Suci (UI Scholars Hub, 2024)
Background: Low back pain (LBP) is pain that is felt in the lower back area, namely between the corners of the lowest ribs and the lower buttocks (lumbar or lumbo-sacral area) and can be local pain or radiate to the upper thighs/legs or both. Low back pain is a 10% debilitating condition that results in a change in life expectancy due to disability. Low back pain is not a malignancy and is a self-limiting condition, but patients always seek treatment to reduce the severity of their symptoms. Chronic Low Back Pain can alter lifestyle and increase the rate of prolonged absenteeism at work resulting in physical limitations. Discomfort due to chronic low back pain is a sign that requires immediate treatment. Methods: The purpose of this evidence-based case report is to get the right answer about McKenzie exercise in reducing low back pain in office workers. Article searches were conducted through PubMed, Embase and Cochrane Library. Inclusion criteria were Systematic Review, Meta-Analysis, Randomized Control Trial (RCT), Adult or Productive Age, Non Specific Chronic Low Back Pain and McKenzie Exercise. Then critically reviewed using Oxford CEBM criteria for intervention-therapy studies Results: 1 research article was obtained that met the inclusion criteria with the type of Randomized Control Trial (RCT). Conclusion:. The critical review showed that McKenzie exercise can reduce complaints of low back pain at 5 weeks of treatment, but this exercise did not show a clinical effect in the form of a reduction in complaints of low back pain after being implemented for 3,6 and 12 months. Keywords: Low Back pain; McKenzie; Exercise